Reef Geomorphology and Associated Habitats of Karimunjawa Islands, Indonesia: A Spatial Approach to Improve Coastal and Small Islands Management - Tubagus Solihuddin; Dwi Amanda Utami; Hadiwijaya Lesmana Salim; Eva Mustikasari (Pusat Riset Kelautan, 2020)
The Karimunjawa Islands are situated in the offshore of Jepara region of Central Java with abundant coastal and marine resources including coral reefs. The reef geomorphology appears typical of fringing reefs worldwide comprising reef flat, reef crest and reef slope. The reef geomorphic profiles are generally gently sloping seaward with slightly raised reef crest along the reef edge. The reefs slope moderately (15-30°) at the upper forereef slope ( 5-10 m depth) and tend to drop steeply, sometimes almost vertical, at depths of 10-30 m. The coral communities are found from the intertidal to a depth of about 15 m, with the most vigorous development occurring between 1.5 to 5 m. The reef flats have low coral cover and are extensively covered by a mixture of seagrass beds and carbonate sand. The reef crests, which mark boundaries between reef flat and upper forereef slope, are mainly colonized by mixed Acropora corals, mainly A. Hyacinthus. The forereef slopes have substantial coral growth prevailing mixed branching Acropora, Porites cylindrica and Porites sp. Sediments on the reef flats are mainly bioclastic materials derived from reef-erosion, including coral fragments, mollusks, foraminifera, red algae, Halimeda, Echinodermata, aggregate, quartz, and lithic fragments. Seagrass beds, mainly Enhalus, occur on the inner reef flat and are gradually shifted to macroalgae, predominantly Sargassum. The study provides a basic requirement for fisheries management and environmental monitoring for a mid-Sunda Shelf within a biodiversity “hotspot”.